EXPLORING THE ROLE OF INFLUENCER MARKETING IN SHAPING CONSUMER TRUST AND BRAND IMAGE - Ayu Amrita, Nyoman Dwika (KRIEZ ACADEMY : Journal of development and community service, 2025)
Background:Influencer marketing has transformed the way brands connect with audiences, leveraging the power of authenticity, storytelling, and engagement to build trust and shape brand perception. As consumer expectations evolve, transparency and measurable outcomes have become critical in determining the effectiveness of influencer campaigns. Aims:This study aims to explore the role of influencer marketing in enhancing consumer trust and brand image, with a focus on authenticity, storytelling, and transparency. It also examines the challenges in measuring the impact of influencer marketing and offers practical recommendations for optimizing strategies. Research Method:A mixed-methods approach was employed, integrating quantitative surveys and qualitative interviews. Data were collected from 400 participants, including marketing professionals, influencers, and consumers, to analyze the impact of key elements such as engagement, transparency, and storytelling. Statistical analysis and thematic exploration were used to derive meaningful insights. Results and Conclusion:The findings reveal that authenticity and storytelling significantly enhance consumer engagement and trust, with 70% of respondents favoring influencers who share relatable narratives. Transparency emerged as a critical factor, with 72% of consumers valuing clear disclosures. However, challenges such as tracking ROI and balancing promotional content were identified. Addressing these issues through advanced analytics and strategic alignment can unlock the full potential of influencer marketing. Contribution:This study provides a comprehensive framework for understanding the dynamics of influencer marketing, offering actionable insights to optimize campaigns and align them with consumer expectations. It bridges theoretical concepts with practical applications, enhancing the effectiveness of influencer strategies.